Exploring the Direct & Indirect Costs of Accident: An Empirical Analysis for KVMRT Projects in Malaysia - Mohd Kamar, Izatul Farrita; Che Ahmad, Asmalia; Kasiron, Mohd Yusof (International Journal of Sustainable Construction Engineering and Technology, 2023)
The Klang Valley Mass Rapid Transit (KVMRT) System is set to be one the most important and largest transport infrastructure projects in Malaysia. Since its inception in 2011, the rapid development of the KVMRT System has contributed to a substantial amount of costs related to safety and health issues. Fatalities, serious injuries, and damage to properties have occur every year due to the rapid construction of this project. Work injuries create significant economic and humanitarian consequences to our society, especially to this project where it involves billions of Malaysian Ringgit (RM). The awareness of the accident, especially the payment cost, is absent because the contractors, clients and the consultants leave these matters to the insurance company. They always ignore the indirect costs due to an accident without realising the true losses to them. Therefore, this paper studies the types of indirect costs of accident incurred during the construction of KVMRT Projects. Sixty (60) reported accident cases were examined to measure the level of significance for those items from the safety personnel experiences. The study found that the most significant type of accident contributing to the indirect costs is the Management Cost Component and Accident Report Cost where it involved the cost of the investigation process item until to the preparation of report. The findings of the study may assist stakeholders in estimating the accident costs during construction projects, and, hence, enable them to plan their investments in terms of safety measures in a more insightful manner.